Persepsi mahasiswa pgsd terhadap pentingnya mata pelajaran bahasa inggris bagi siswa sekolah dasar di era globalisasi - Iveb Rizky Emilia; Siti Wahyuningsih; Suharno Suharno (Universitas Sebelas Maret, 2021)
The goal of this research is to know how is PGSD FKIP UNS students perception about yhe importance of English lesson in elementary school in this globalization era. This research are included by qualitative research. The research data are obtained from questionnaries, interviews and document analysis. Then, calculated by using validity and triangulation. The result of this research are most of them having an opinion yhat English lessons in elementary school in globalization era is an important things to learn. Other than that, English should be learned in elementary school because in this era english are used in ecery part of life even if on a severe things. Student in elementary school are suitable to learn about grammar and vocabulary, so in the next step they are able to learn it more